Michoacán : tesoros - Franco, José Antonio (dir.); Aguilar, Irma (texto); Ultreras, Bertha (texto); Díazmuñoz, Ricardo (texto); Navarro, Jaime (fotógrafo) (2006)
Guía de hoteles y restaurantes ubicados en Michoacán en edificios de valor patrimonial.